John Barth's later fiction : intertextual readings, with emphasis on Letters (1979) - Nas, Aloysia Antonia Sophia Maria (Department of English Language and Literature, 2016)
This dissertation consists of five chapters. Chapter I serves as an introduction to intertextuality; it focuses on John Barth's narrative crisis and discusses structuralist and poststructuralist theories of intertextuality. Chapters II, III and IV discuss the agencies of reader, author and text respectively. Chapter II looks at structuralist and poststructuralist notions of reading and John Barth's parodic play with these notions; it also provides an in-depth analysis of the external and internal readers of LETTERS. Chapter III concentrates on the roles of the reader as re-writer and the author as re-arranger and looks closely at the roles of the different narratorial agents in LETTERS. Chapter IV starts off with a discussion of the discourse of the copy in postmodern culture and moves, via poststructuralist and narrativisit mimesis, to different forms of repetition as developed by Soren Kierkegaard, Martin Heidegger and Jacques Derrida. Chapter V focuses on John Barth's rethinking of notions of authorship and authority. It first gives an historical introduction to authorship, starting off in the Middle Ages, and then moves, via eighteenth-century Samuel Richard, son and nineteenth-century Edgar Allan Poe and Soren Kierkegaard, to twentieth-century· notions of authorship as developed by Harold Bloom, Michel Foucault and Jonathan Culler,to end with Jacques Derrida's signature theory. Bibliography: p. 340-356.